Problemas de salud asociados al riego agrícola con agua residual en méxico - Guillermo Ruiz (Salud Pública de México, 1993)
Over 85 000 hectares in the Mezquital Valley of central Mexico are irrigated with wastewater. The main crops are fodder and cereal crops. A two cross-sectional survey was carried out to test the impact of exposure to raw wastewater and from storage of that wastewater in reservoirs. The main outcomes were Diarrhoea disease and parasitic infections in farmworkers and their families. The total study population in the dry season included 2 049 households. The study population was classified in households where the farmworker is exposed to untreated wastewater (exposed group), households exposed to reservoir water (semi-exposed group), and households where the farmworker practices rainfed agriculture (control group). Preliminary analysis of the data has been carried out. Current information indicates that the risk of Ascaris lumbricoides infection is much higher in the exposed group than in the control group (95% CL= 4.0-67.3 and 4.7-78.8). According to the procedures employed, exposed children from exposed households were at higher risks of Diarrhoea disease than controls (95% CL= 1.03-2.03). The final results of this study are expected to aid decisions within the reuse programmes in developing countries